Conhecimentos docentes para educação on-line : contribuições de um curso de formação em EaD da UFSCar - Nazário, Kenia Rosa de Paula (Universidade Federal de São Carlos, 2015)
Social changes today involve new paradigms in various sectors of society. Among them, there has been a change in the education setting, as the Information and Communication Digital Technologies (TDIC) with its several new possibilities of teaching and learning. To understand these possibilities the teacher training area has sought to follow these new demands with regard to initial and continuing education to subsidize teachers into these technological resources. In this sense, the teaching knowledge base tends to be reconfigured embracing new learning for teachers towards building autonomy, transformation and emancipation. In this context, this study aims to understand how the participation of teachers of a Public Higher Education Institution (IPES) in a continuing education course in distance education, fully distance, can contribute to teaching learning, redefining the knowledge base of these participants and targeting their professional development. For this qualitative nature study, we have chosen a methodology developed in two stages in which data were collected. The first one was to apply an online questionnaire, which was answered by graduates participating in the Teacher Training Course in distance education offered by the Coordination of Development and Professional Improvement of the General Secretariat of Distance Education at UFSCar. In the second stage, data were taken in the virtual environment of that course, specifically in daily activity that contains the individual narratives posted by the participants of the course. The analyzes show that the articulation of the specific content and the TDIC is not trivial, it is a process that needs time, support and subsequent trials towards the achievement of the desired goals and knowledge of pedagogical and technological content, as proposed by the TPCK model. Data indicate that the course brought contributions to the teaching practice in the classroom and in distance learning, especially with regard to planning, management, interaction and integration of digital technologies in the classroom. It is believed that the duration of the course is not enough to fully attain the process of teaching learning; on the other hand, it should be an opportunity of awareness for teachers to reflect on such issues and considerations that should be further and continuously developed in different learning spaces.
Keywords: Formação de professores em EaD; Tecnologias digitais da informação e comunicação; Desenvolvimento profissional docente; CIENCIAS HUMANAS::EDUCACAO